Defining Learning in Educational Leadership: Reframing the Narrative. (October 2019) - Myran, Steve; Sutherland, Ian
Purpose: The purpose of this article is to reframe our field's narrative around the science of learning. We seek to (1) describe the patterns within educational leadership and administration that are conceptually tethered to scientific management and highlight the absence of clearly defined conceptions of learning, (2) provide a synthesis of the science of learning, and (3) offer a "progressive problem shift" that promotes such a reframing.Methods: An integration of theory building methods with problem posing/identification strategies is designed to deconstruct the field of educational leadership through a science of learning lens and build toward theory that is more adaptive to our goals of leading for learning.Findings: Our findings stem from the central observation that educational leadership and administration has to date produced no conceptual or explicit operational definition of learning. Lacking such a definition, the field has been vulnerable to outlooks about learning that default to assumptions notably shaped by scientific management. This is in contrast to our review of the learning sciences literature, which emphasizes that learning is dependent on the active and deliberate agency of the learner and a host of introspective outlooks and behaviors and that these individual learning characteristics are situated within complex and dynamic social contexts that serve to mediate and shape learning.Implications and Conclusions: We argue that the future of our field rests, in large measure, on our ability to address the incongruences between our field's foundations in scientific management and the science of learning.